Some subclasses of univalent functions associated with $k$-Ruscheweyh derivative operator - Seoudy, T. M. (Ukrains’kyi Matematychnyi Zhurnal, 2022)
UDC 517.5The purpose of the present paper is to investigate some subordination, other properties and inclusion relations for functions in certain subclasses of univalent functions in the open unit disc which are defined by $k$-Ruscheweyh derivative operator.